A Petri Net Modeling Framework for the Control of Flexible Manufacturing Systems. Issue 13 (2019) - Wenzelburger, Philipp; Allgöwer, Frank
Abstract: The changes in manufacturing practice towards increasingly flexible structures demand novel strategies for production scheduling and control. To this end, we introduce an automated model generation scheme that builds upon a coarse description of the production process and the factory. The generated model is based on a Petri Net representation of the production process, which we slightly enhance to separate automatically evolving processes from consciously taken manufacturing decisions. From the Petri Net model we deduce a state space description which can be used for the synthesis of feedback control for the manufacturing system. The model generation is illustrated with an example and further possibilities to utilize and enhance the model are discussed.